EMPOWERMENT: CROWDFUNDING SEBAGAI INOVASI WAKAF UANG DENGAN ANALISIS PEMBIAYAAN AL-QARD - Uswatun Hasanah; Delli Ridha Hayati (EKSYDA: Jurnal Studi Ekonomi Syariah, 2020)
Money waqf is an elegant innovation with productive and innovative management so that cash waqf can be collaborated with fintech which refers to the internet platform, namely crowdfunding using al-qard financing contracts to create capital for the community in micro-businesses, this will stimulate and educate the public and create prosperity in in all fields, especially socio-economic, that way the community will recognize the potential and use the potential productively and communicatively. This research is a qualitative descriptive which will describe the public still lacking education about cash waqf which can be used as capital for micro businesses.